2021
DOI: 10.3389/fpsyg.2020.594086
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of COVID-19 Lockdown 1.0 on Working Patterns, Income, and Wellbeing Among Performing Arts Professionals in the United Kingdom (April–June 2020)

Abstract: This article reports data collected from 385 performing arts professionals using the HEartS Professional Survey during the COVID-19 Lockdown 1.0 in the United Kingdom. Study 1 examined characteristics of performing arts professionals’ work and health, and investigated how these relate to standardized measures of wellbeing. Study 2 examined the effects of the lockdown on work and wellbeing in the respondents’ own words. Findings from Study 1 indicate a substantial reduction in work and income. 53% reported fina… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
117
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 86 publications
(151 citation statements)
references
References 59 publications
18
117
2
Order By: Relevance
“…I'm not, I'm not stressing about [the diary service] coming off my phone thinking 'oh what's that work' or 'my whole life is clashing again"' (M11), and another player commented "It's amazing when the phone doesn't go, you know it's because you haven't fucked up, it's because the phone can't go" (S9). Notably, most of these participants reporting less anxiety and feeling more relaxed were in the seasoned group, and all three mid-career participants and five of the eight seasoned participants had received government financial aid, suggesting that this may have helped to alleviate some of the stress of financial hardship, found to be related to lower wellbeing in performing arts professionals during this period (Spiro et al, 2021). Five participants in the present study (M = 1, S = 4) reported that this period had provided an opportunity for their bodies to recover from the strains of playing, supporting evidence of the presence of performance-related physical problems among orchestral musicians (Kok et al, 2016): "Physically I'm recovering from the strains of aches and pains, so that side of things is better, yeah" (S1).…”
Section: Opportunities and Positivesmentioning
confidence: 97%
See 4 more Smart Citations
“…I'm not, I'm not stressing about [the diary service] coming off my phone thinking 'oh what's that work' or 'my whole life is clashing again"' (M11), and another player commented "It's amazing when the phone doesn't go, you know it's because you haven't fucked up, it's because the phone can't go" (S9). Notably, most of these participants reporting less anxiety and feeling more relaxed were in the seasoned group, and all three mid-career participants and five of the eight seasoned participants had received government financial aid, suggesting that this may have helped to alleviate some of the stress of financial hardship, found to be related to lower wellbeing in performing arts professionals during this period (Spiro et al, 2021). Five participants in the present study (M = 1, S = 4) reported that this period had provided an opportunity for their bodies to recover from the strains of playing, supporting evidence of the presence of performance-related physical problems among orchestral musicians (Kok et al, 2016): "Physically I'm recovering from the strains of aches and pains, so that side of things is better, yeah" (S1).…”
Section: Opportunities and Positivesmentioning
confidence: 97%
“…and that discrimination against self-employed is, is really hurtful, when we're all supposed to be in it together. (S9) Notably, the majority of respondents to Spiro et al's (2021) survey of performing arts professionals in the UK also reported loss of work, worry about finances and uncertainty and concern about the future. One participant in the present study talked openly about her frustration and jealousy of those people who she felt were oblivious to the impact of COVID-19 on people's lives: "I find it quite hard to be in touch with people who are not doing the same, who don't have the same jobs as us.…”
Section: Anxietymentioning
confidence: 99%
See 3 more Smart Citations